2017
DOI: 10.1186/s12877-017-0525-1
|View full text |Cite
|
Sign up to set email alerts
|

Rest-activity rhythms in small scale homelike care and traditional care for residents with dementia

Abstract: BackgroundAn enriched environment for residents with dementia may have a positive effect on the rest-activity rhythm. A small scaled homelike special care unit might be such an enriched environment. The present study shows whether the rest-activity rhythm of residents with moderate to severe dementia responds positively to a transfer from a regular Special Care Unit (SCU) to a small scaled homelike SCU.MethodsInitially, a group of 145 residents living in a regular SCU participated. Out of this group, 77 reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 56 publications
0
19
0
1
Order By: Relevance
“…Research has shown that the Self 1 is preserved among persons with advanced dementia. Even when they almost entirely answer "yes" or "no" to questions, they still show that they can experience themselves as "I" (32,60). Still it seems reasonable to suggest that we can help persons preserve their feeling of being an I by making them feel that they are seen and listened to, that is that they are.…”
Section: Strengthening Self 1 Communionmentioning
confidence: 99%
See 4 more Smart Citations
“…Research has shown that the Self 1 is preserved among persons with advanced dementia. Even when they almost entirely answer "yes" or "no" to questions, they still show that they can experience themselves as "I" (32,60). Still it seems reasonable to suggest that we can help persons preserve their feeling of being an I by making them feel that they are seen and listened to, that is that they are.…”
Section: Strengthening Self 1 Communionmentioning
confidence: 99%
“…The understanding of how important the experience of at-homeness is for our sense of self and well-being has led to an endeavor to create care environments where persons with advanced dementia can feel at home. However, although carers try to furnish the rooms as homely as possible it is often hard to document positive effect on the persons' daily life (59). Observation of nursing home residents with advanced dementia showed that they alternated between expressing feeling at home (at-homeness) and not feeling at home (homelessness) both verbally and nonverbally.…”
Section: Moments Of Homecomingmentioning
confidence: 99%
See 3 more Smart Citations